A Mixed Methods Research Strategy to Study Children's Play and Urban Physical Environments in Dhaka. (July 2020) - Bhuyan, Md Rashed; Zhang, Ye
Mixed methods research (MMR) is useful for addressing complex and multidisciplinary urban problems. This article demonstrates an integrated MMR approach with a novel two-phase exploratory sequential design while studying play, play space, and children's (age 7-15 years) location preference for play in three residential areas in Dhaka. We used directly administered survey and interviews in the first phase to describe play and play space from children's perspective. Informed by the first, we employed GIS-based spatial and statistical analysis in the second phase to study patterns of children's location preference for play. Our article contributes to the methodological literature by combining MMR with urban spatial analysis in children's play environment studies.